(untitled) (Clío & Asociados. La historia enseñada. ISSN: 2362-3063, 2018)
The subject Didactic Planning and Practices of teaching in History is part of the last cycle of Teacher Training in History of the National University of La Plata. Within the framework of the course, educational outings are proposed, among other activities, as an educational activity that enriches the teaching process. These are a methodological strategy that opens the debate around other ways of ‘inhabiting’ the University and the school to promote pedagogical didactic alternatives that interpellate the established academic and school format and invite future teachers to propose them in their own classes, both in the residence and in their next professional practice. They make it possible to approach how museums and the different urban spaces with their monuments and their brands are vehicles of memory. They do not ensure by themselves the contents to be transmitted nor the meanings with which they will be interpreted, since these depend on the recipients, on the readings and appropriations that they make. The route we propose involves reflecting on the marks of memory and looking with different eyes at the spaces lived and traveled daily. The work develops the shared experiences in the Museum of Natural Sciences of the City of La Plata and the Ethnographic Museum of the City of Buenos Aires.